THE SANOGEN AND THE CORPORAL POSTURE - Vizitiu Elena; Constantinescu Mihai (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article presents some general aspects that are based on an ongoing study on the choice of therapeutic swimming as a primary means of recovering or rehabilitating postural physical deficiencies in children during growth and development.